MODERNISING THE EU-TURKEY CUSTOMS UNION AS AN INTEREST-DRIVEN INITIATIVE - (:unkn) unknown (ANKARA UNIV EUROPEAN UNION RESEARCH CENTRE, 2020)
The customs union (CU) established in 1996 between the EU and Turkey has always been regarded by the Turkish side as the main device for eventually achieving full EU membership as envisaged by the Association Agreement of 1963. Currently, in the absence of a well-defined and strong membership prospect, continued structural deficiencies of the CU and global pressures force both parties to modernise the CU to meet their shared economic interests and high level of interdependence. This paper explains why and how the parties need to modernise the CU and discusses political difficulties before the modernisation process. The paper reveals that the parties' preferences regarding modernisation and the specific parameters that negotiations may depend on are mainly generated by the domestic interests of societal actors.
Keywords: Customs Union; modernisation of the Customs Union; liberal intergovernmentalism; EU-Turkey relations; PREFERENCES